Analysis of malaria during the viceroyalty in the traditions «El rosal de Rosa» and «Los mosquitos de santa Rosa» - Vizcarra Checya, Maely Mishell (2023)
This article will analyse the incidence of malaria in Peru from the time of the Viceroyalty to the present day. It will be based on the mentions of this disease in the traditions «El rosal de Rosa» and «Los mosquitos de santa Rosa» by Ricardo Palma. It will also identify the regions where the highest incidence of malaria cases is found, the symptoms that arise from the mosquito bite, the treatments that are rooted and up to date; finally, it will trace how the viceregal society contracted this disease and will review the measures that are taken nowadays to control it.